2011
DOI: 10.1111/j.1365-2044.2011.06752.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A‐induced rhabdomyolysis and acute kidney injury complicated by posterior reversible encephalopathy syndrome

Abstract: SummaryWe report a case of Influenza A‐induced rhabdomyolysis causing acute kidney injury in a young adult female who required invasive ventilation and renal replacement therapy. This case was further complicated by posterior reversible encephalopathy syndrome. Although this represents an extremely rare neurological complication of Influenza A infection, an appreciation of the condition and its management is important, given the high numbers of critically ill patients recently affected by H1N1 Influenza A in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Accordingly to Naranjo's probability scale a probable relationship between levofloxacin and rhabdomyolysis (total score 5) was confirmed even if simvastatin was considered to be an alternative cause of the adverse event (Table 1). Furthermore, all other potential reasons of muscle damage, such as Influenza A and B virus [11], Parainfluenza type 1 and 2 virus [12], Coxsackie virus [13], HIV 1-2 virus [14], endocrinological abnormalities [15], and autoimmune myositis could be serologically excluded. Serum and urinary antigen and antibodies exams excluded Legionella pneumophila , Mycoplasma pneumoniae , Chlamydia pneumoniae , and Streptococcus pneumoniae as potential pathogens of the community acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly to Naranjo's probability scale a probable relationship between levofloxacin and rhabdomyolysis (total score 5) was confirmed even if simvastatin was considered to be an alternative cause of the adverse event (Table 1). Furthermore, all other potential reasons of muscle damage, such as Influenza A and B virus [11], Parainfluenza type 1 and 2 virus [12], Coxsackie virus [13], HIV 1-2 virus [14], endocrinological abnormalities [15], and autoimmune myositis could be serologically excluded. Serum and urinary antigen and antibodies exams excluded Legionella pneumophila , Mycoplasma pneumoniae , Chlamydia pneumoniae , and Streptococcus pneumoniae as potential pathogens of the community acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated creatine kinase (CK) has been implicated as a contributing factor for AKI in pH1N1 [14,17,22,28]. Pettila et al reported that 15.8% of AKI patients had CK levels exceeding 5000 IU/L and found a trend of increasing CK levels with worsening AKI [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports have described the incidence and outcomes of AKI among critically ill adult and pediatric pH1N1 patients [13]–[28]. Many studies, however, were limited by design (case reports [14,17,20,22,24,28] or small case series [13,15,18,21,27]), small sample size [16,19,25], or single-center enrollment [13,15,16,18,21]. There have been few larger scale prospective multi-center cohorts [19,23,26], none of which described the Canadian pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital disorders of metabolism of organic and fatty acids may be rapidly exacerbated by influenza, mimicking acute encephalopathy . There also are case reports of acute encephalitis with refractory, repetitive partial seizures (AERRPS), and posterior reversible encephalopathy syndrome (PRES) …”
Section: Major Syndromes Of Influenza Encephalopathymentioning
confidence: 99%